PENGARUH KOMPONEN-KOMPONEN SERVICE QUALITY TERHADAP KEPUASAN KONSUMEN PADA CAFÉ ONE ELEVEN CAFFEINE DEALER GROBOGAN - Vania Thahirah; Surono Surono (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Increasing consumer satisfaction with purchases is the ultimate goal of endeavor in the culinary business. This study aims to identify whether a tangibility, reliability, responsiveness, anssurance, and empathy can affect the level of consumer satisfaction at Café One Elevent Dealer Grobogan. The authors took a sample of 140 respondents of quantative and descriptive methods, which described the relationships between the phenomena studied systematically, factually and accurately. In data processing and analysis, the author uses the Partial Least Square (PLS) analysis method using the SmartPLS 3 application. The results in this study that partially all variables of tangibility, reliability, responsiveness, anssurance, and empathy have a positive effect and significance on customer satisfaction of Café One Eleven Caffeine Dealer, with a fit model fit of 77%. The results in choosing the contribution of efficiency of this study there are factors or methods to the culinary business unit to increase consumer satisfaction of the culinary business.